Cruel crown - Aveyard, Victoria (Aveyard, Victoria. Red queen, 2016)
In "Queen Song," Queen Coriane keeps a secret diary that recounts her heady courtship, Cal's birth, and the challenges in her royal life; and in "Steel Scars," Captain Farley is tasked with planting the seeds of rebellion in Norta.